Special Features in Expressing the ‘Homeland’ Concept in the Yakut Heroic Epic Olonkho - Savvinova, Gulnara Egorovna (Journal of History Culture and Art Research, 2018)
Presently, the study of epic texts is undergoing one of the most significant stages of its development, i.e., a theoretical basis is being created and established. The theoretical category of epic studies is being thoroughly revisited from the point of view of its objectiveness, its ontological and specific nature, as well as its functionality and importance in the field of epic studies in general. Due to the growing interest in the humanities among scholars in the modern academic research society, the 21st century is unfolding in an essentially new research environment, which needs to be revisited and analyzed. The necessity to study the existing status of the topic under discussion is first of all justified by the fact that it encompasses a process of qualitative changes in the epic text representations, epic texts being a subject of humanitarian, historical and cultural studies; this is one of the key aspects in the epic studies as a whole and in the study of Yakut heroic epic olonkho in particular. In the process of its establishment in the oral folklore tradition, the Yakut heroic epic olonkho underwent a process of transformation from a heroic epic to a philosophical and didactical one. The “multi-layer” content of the Yakut olonkho, which includes in itself the archaic and worldview components of the Yakut peoples’ culture, is a unique source for the historic and typological renewal of the various examples of traditional art, which is obliquely depicted in the epic texts. Currently, a large scope of historical and graphical materials, literature on the study of the worldview depicted in the Yakut olonkho is easily accessible. The study of the world creation in the Yakut olonkho about the Middle World, and the native land in particular, where the bogatyr lives, is one of the main categories in theoretical epic studies. The present article describes distinctive features in the depiction of the main character’s homeland in Yakut epic olonkho in the context of a comparative study. By distinguishing its unique features in the image depiction of the main character’s homeland, the role that the latter plays in the Yakut olonkho, we provide ourselves with an opportunity to reconstruct a traditional world representation, which would allow to achieve a better understanding of the outlook that the Yakut people had about themselves and the world in the ancient times.